In-vitro inhibitory effect of Cinnamomum zeylanicum and Eugenia caryophyllata Oils on Multispecies Anaerobic Oral Biofilm - Azizan N.; Mohd-Said S.; Firdaus Mazlan M.K.; Chelvan K.T.; Zainal-Abidin Z.; Rohazila Mohamad Hanafiah (University of Dicle, 2024)
Indexed by SCOPUS